Security and Disadvantages of the Digital Economy - Abdurakhmonov Abdulaziz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The government is understood less than the traditional functions of government regulation, including the best practices of regulation, how to evolve with these transformational changes and how to say. Therefore, it is very important to participate in such work, especially digital transformation is an ongoing regulatory process that creates needs that require rules. Areas such as retail, finance, communication and entertainment are already "numbered" in many countries.